Diversity and Discontent: The Relationship Between School Desegregation and Perceptions of Racial Justice - Brooks, Richard R. W. (2006)
A number of recent studies have explored the consequences of interracial peer effects on the academic and social performance of minority students. This article contributes to that discussion, focusing, however, on perceptions rather than behaviors. The analysis suggests that exposure to white peers is associated with declining perceptions of racial justice among black and Latino high school students. While cautioning against causal interpretations of this finding, the article suggests that the integrationist aims of Brown v. Board of Education will not be satisfied without more thoughtful and vigorous desegregation efforts